Design of Power Pole Delivery Distribution in a Business Project at PT XYZ Bandung Branch Using DMAIC Method - Muhamad Nailul Hikam; Muhamad Rizal; Nurillah Jamil Achmawati Novel (SKeTsa Bisnis (e-jurnal), 2025)
Introduction; This study aims to identify the causes of delays in the distribution of electricity pole shipments in the PT XYZ Bandung Branch project and formulate improvement solutions. Method; This research was conducted through the Six Sigma DMAIC (Define, Measure, Analyze, Improve, and Control) approach to identify the distribution process, measure current performance, classify and analyze the root causes of problems causing delays, and design improvements with the aim of minimizing delivery delays in similar projects. Result; The results showed that there were three main causes of delay with a contribution of 68% to the twelve causes of delay. In this study, a DPMO value of 20,833 was obtained with a sigma level of 3.5. Conclusion; Researchers suggest taking corrective action with 5W + 1H analysis based on the root cause of the problem. The implementation of these improvements is expected to increase the efficiency of the electric pole distribution process and company guidelines supported by continuous supervision.